Crítica ao fundacionismo cartesiano com base no argumento contra a linguagem privada - Capistrano, Pablo Moreno Paiva (2003)
This assignment ains to prove the pertinency of using the wittgenstein´s argument against private language as a criticism to cartesian fundacionism. Therefore, I want to demonstrate in the first chaper the conceptual viability of facing the cartesian argument of cogito not as a simple silogism but as an exemple of a private experience (process of thinking). At the second chaper, the subordination of the argument against private language give us the idea that rules can only be followed by means of corrections givem by a linguistic community that is external to the private subject, in a way to be unviable the assumption that is possible to name an internal experience without searching external rules of the use of terms. At the chaper 3 the pertinency of the hypothesis raised by A. Kenny, about the overtaking of the argument against private language can be extended to the idea of epistemic and ontologic privacy that would lend validity to the fundacion present at the argument at the cartesian cogito. In oder to become evident the pertinency of use of Wittgenstein´s argument agaist Descartes´ fundation, it´s necessary, at the chaper 3, to demonstrate the impertinency of the objection to the A. Kenny´s hypothesis, based on the experiency of the thought of the brain at the recipient, to make clear the incompatibility existing between the cartesian idea of cogito and Wittgenstein´s notion that language is an activitie followed by rules, wich correction criterion may be external and intersubjective